Development of Disaster Mitigation Interactive E-Modules Based on Socio-Scientific Issues (SSI) to Facilitate Junior High School Students’ Science Literacy - Islami, Nofenka Permata; Setiawan, Agung Mulyo (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
In the 21st century, scientific literacy is crucial for students as it connects science to real-life issues. The Socio-Scientific Issues (SSI) approach can be used through contextual learning to enhance students’ scientific literacy. This approach involves developing teaching materials based on SSI and for this research, the focus is on disasters and mitigation to increase preparedness in disaster-prone areas. The research aims to develop and test the feasibility and practicality of SSI-based teaching products using the Research and Development (R&D) method, specifically the ADDIE model. The novelty of the SSI e-module is in the issues discussed, the interactive and varied material, and the quiz features. These can improve students’ scientific reasoning by involving them in real-life problem-based discussions relevant to everyday life, thus encouraging critical analysis, decision-making, and collaborative problem-solving.Data was collected through interviews with teachers to analyze their needs and through questionnaires distributed to students, feasibility tests, and product practicality tests. The results showed 90% material feasibility, 100% concept correctness, 95% media feasibility, and 96% question feasibility, all falling within the "very feasible" category. Additionally, an empirical test of the questions through validity testing resulted in 10 valid and 5 invalid questions, with a reliability test yielding a score of 0.717.The score is included in the high category, it needs to be increased to the very high category (0.80 â‰¤ r â‰¤ 1.00) by evaluating the material, design, and structure of the module. The product’s practicality was tested on 2 science teachers and 32 class VIII students, and achieved percentages of 94% and 89% respectively, categorizing it as "very practical". In conclusion, the e-modules developed in this research are deemed very feasible and practical for facilitating scientific literacy in students.